Proposed Exercises Using Flexible Resisters And Their Effect On Developing Strength Endurance And The Performance of Some Offensive Skills In Youth Basketball - Mohameed, Omer; Mohameed, Laith (Journal of Physical Education, 2017)
The importance of the research lies in using flexible resistors in developing strength endurance and performing some offensive skills in basketball. The problem of the research lies in physical preparation was very poor during special preparation phase. The researchers used the experimental method. The subjects were (8) u18 basketball players from the national center for gifted in basketball season 2015 – 2016. The data was collected and treated using proper statistical operation to conclude that physical training using flexible resistors was more effective in developing physical performance and skill. Finally they recommended the necessity of dedicating time to develop the physical aspects as well as training physical abilities using flexible resistors.